Sahaba Initiative sebagai Organisasi Nirlaba dalam Menjaga Harmonisasi dan Toleransi Antar Manusia di Negara Minoritas - Hikmah, Sofi Faiqotul; Kholiq, Ilham Nur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The research conducted at Sahaba Initiative California aims to analyze how Sahaba Initiative as a non-profit organization maintains harmony and tolerance between people in minority countries. The research method is descriptive from data taken through various journals, books, and data from the field. The results of the study show that the values of tolerance and harmony in Sahaba Initiative are reflected in the Al-Quran Surah Al-Maidah Verse 2, Al-Hujurat Verse 10, Al-Hujurat Verse 13, Al-Mumtahanah Verse 8-9, Al-Kafirun Verse 6. The values and principles of tolerance carried out by Sahaba Initiative as a non-profit organization have 4 components, namely the value of mutual assistance, the value of tolerance, the value of anti-violence, and the value of acceptance of tradition.